Never grow up - Kingsbury, Karen; Russell, Tyler; OverDrive, Inc. (New York : Simon & Schuster Books for Young Readers, 2021)
While Kari Baxter eagerly awaits a meteor shower and frets over what she wants to be when she grows up, Ashley gets an idea for how to keep her siblings from growing up too fast.
"A Paula Wiseman Book."
Electronic book.
Ages 8-12.
Grades 4-6.
Electronic reproduction.
Keywords: Advantage title -- Fiction; Family life -- Fiction; Siblings -- Fiction; Meteor showers -- Fiction; Christian life -- Fiction; Electronic books